Ciliate epibionts associated with crustacean zooplankton in German lakes: Distribution, motility and bacterivory - Samantha Lynn Bickel (Frontiers in Microbiology, 2012)
Ciliate epibionts associated with crustacean zooplankton are widespread in aquatic systems, but their ecological roles are little known. We studied the occurrence of ciliate epibionts on crustacean zooplankton in nine German lakes with different limnological features during the summer of 2011. We also measured the detachment and reattachment rates of the ciliates, changes in their motility, and the feeding rates of attached vs. detached ciliate epibionts. Epibionts were found in all lakes sampled except an acidic lake with large humic inputs. Epibiont prevalence was as high as 80.96% on the cladoceran Daphnia cucullata, 67.17% on the cladoceran Diaphanosoma brachyurum, and 46.67% on the calanoid copepod Eudiaptomus gracilis. Both cladoceran groups typically had less than 10 epibionts per individual, while the epibiont load on E. gracilis ranged from one to >30 epibionts per individual. After the death of the zooplankton host, the peritrich ciliate epibiont Epistylis sp. detached in an exponential fashion with a half-life of 5 min, and 98% detached within 30 min, leaving behind the stalks used for attachment. Immediately after detachment, the ciliates were immotile, but 62% became motile within 60 min. When a new host was present, only 27% reattached after 120 min. The average measured ingestion rate and clearance rate of Epistylis were 11,745 bacteria ciliate-1 h-1 and 24.33 μl ciliate-1 h-1, respectively. Despite their high feeding rates, relatively low epibiont abundances were observed in the field, which suggests either diversion of energy to stalk formation, high metabolic loss by the epibionts, or high mortality among the epibiont populations.